The regulation of yes-associated protein/transcriptional coactivator with PDZ-binding motif and their roles in vascular endothelium - Zhang, Wen; Li, Qian-qian; Gao, Han-yi; Wang, Yong-chun; Cheng, Min; Wang, Yan-Xia (Frontiers in Cardiovascular Medicine, 2022)
Normal endothelial function plays a pivotal role in maintaining cardiovascular homeostasis, while endothelial dysfunction causes the occurrence and development of cardiovascular diseases. Yes-associated protein (YAP) and its homolog transcriptional co-activator with PDZ-binding motif (TAZ) serve as crucial nuclear effectors in the Hippo signaling pathway, which are regulated by mechanical stress, extracellular matrix stiffness, drugs, and other factors. Increasing evidence supports that YAP/TAZ play an important role in the regulation of endothelial-related functions, including oxidative stress, inflammation, and angiogenesis. Herein, we systematically review the factors affecting YAP/TAZ, downstream target genes regulated by YAP/TAZ and the roles of YAP/TAZ in regulating endothelial functions, in order to provide novel potential targets and effective approaches to prevent and treat cardiovascular diseases.